2010
DOI: 10.1021/jp103163f
|View full text |Cite
|
Sign up to set email alerts
|

Why is Pt4+ the Least Efficient Cationic Cluster in Activating the C−H Bond in Methane? Two-State Reaction Computational Investigation

Abstract: The two-state reaction mechanism of Pt4 + with CH4 on the quartet and doublet potential energy surfaces has been investigated at the B3LYP level. Crossing points between the potential energy surfaces are located using different methods, and possible spin inversion processes are discussed by means of spin−orbit coupling (SOC) calculations. As a result, after the C−H insertion intermediates, two distinct H2 elimination reaction paths have been found, and the second C−H bond broken is regarded as the rate-determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0
4

Year Published

2011
2011
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 64 publications
1
18
0
4
Order By: Relevance
“…The calculated structures and spectra, with assignments, that provide the best match to the experiment are shown for the Pt n CH 4 + complexes. The calculated vibrational frequencies are scaled by a factor of 0.97. desorption is consistent with the calculations of Lv et al, [13] who reported the transition state (TS) for Pt 4 + insertion into a C À H bond to be higher in energy than the separated species, in contrast to Pt 3 + , where this TS lies slightly lower in energy than the separated molecules. Entropic factors may also be important, given that the number of pathways for dissociation are presumably much greater than for dehydrogenation.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…The calculated structures and spectra, with assignments, that provide the best match to the experiment are shown for the Pt n CH 4 + complexes. The calculated vibrational frequencies are scaled by a factor of 0.97. desorption is consistent with the calculations of Lv et al, [13] who reported the transition state (TS) for Pt 4 + insertion into a C À H bond to be higher in energy than the separated species, in contrast to Pt 3 + , where this TS lies slightly lower in energy than the separated molecules. Entropic factors may also be important, given that the number of pathways for dissociation are presumably much greater than for dehydrogenation.…”
supporting
confidence: 92%
“…[7] In the case of small ionic clusters reacting with CH 4 under single collision conditions, Pt n [C,2H] + complexes were found to be the favored products. [8][9][10] There have been a number of computational studies of the interactions of platinum clusters [11][12][13] and surfaces [5,14,15] with methane, primarily using density functional theory (DFT). Such calculations are challenging, owing to the large system size, number of electrons and possible paths, and the fact that several electronic states and crossings between them may need to be treated.…”
mentioning
confidence: 99%
See 3 more Smart Citations